Design Multi Input Automatic Identifier System Class B for Indonesian Fishery - A Sumarudin; Willy Permana Putra; Ahmad Rifai; Agfianto Eko Putra (Research Collaboration Community (RCC), 2020)
The need for technology that can help Indonesian fishermen is needed to improve fishing yields. Based on BPS data Indonesian fishermen dropped from 1.7 million to 64 thousand in 2013. This is due to several factors, including unfavorable professions for fishermen. This is insufficient fishing equipment for fishing. One of them is the need for navigation tools that are easily understood by traditional fishermen and in accordance with the needs in fishing.we propose the design of Class B's Automatic Identifier System (AIS) to help fishermen navigate and find fish points. In this system we also propose determining the point of fish based on information from fishermen who are collectively collected by the fishermen. With this design it is hoped that the fish point can be shared with other fishermen. The result this design, it is expected to be able to assist fishermen in navigating using AIS so that fisherman security with AIS system with multiple sensor can be improved find the point of fish obtained from sending data from several fishermen and collect data weather for safety.